Evaluating the intersection between "green events" and sense of community at Liverpool's Lark Lane Farmers Market. Issue 5 (3rd March 2019) - Zhao, Yahan; Wise, Nicholas
Abstract: More research needs to evaluate links between community psychology and event impacts. Events are not just entertainment focused economic drivers, but gatherings contributing to society, community, and local cultural identity. There is also a need to address "green" philosophies, while visible and widespread, are not just environmentally focused, but also local community focused—concerning elements of social sustainability, belonging and sense of community. This makes the discussion of "green events" relevant to community psychology and local well‐being researchers. The aim of this study is to find other possibilities of how green events could contribute to local community well‐being by investigating how farmer markets unite people to understand how such events reinforce and shape a sense of community. This paper is based on participant observations and semistructured interviews to explore the conceptual notion of sense of community. Three emerged themes are presented: local participation, social atmosphere, and a sense of belonging.